"Functional outcome in pediatric grade IV renal injuries following blunt abdominal trauma salvaged with minimally invasive interventions". Issue 5 (October 2020) - Shekar, P. Ashwin; Ansari, M.S.; Yadav, Priyank; Srivastava, Aneesh
Summary: Background: Non-operative management of higher-grade renal injuries has gradually become accepted in pediatric circles following multiple studies over the past decade which showed good renal salvage rates. However, some children do fail this conservative approach and need interventions which are mostly minimally invasive. There is still paucity of studies on the functional outcomes in this unique subgroup of patients. In this study, we review our management and functional outcome of children with grade IV renal injury due to blunt trauma of abdomen managed with minimally invasive interventions (MII) in a tertiary referral center. Aim: The present study seeks to summarize contemporary management of pediatric grade IV renal injury due to blunt trauma at our tertiary care center and to assess the functional outcomes in the subgroup who needed MII. Materials and methods: A retrospective review was performed on children≤18 years with abdominal blunt trauma managed at our tertiary care facility over the past 10 years (January 2008–January 2018) to identify those with grade IV renal injuries. Data collected included demographic data like age, sex, mechanism of injury, incidence of hematuria, incidence of pre-existing urologic conditions, associated non-renal injuries, transfusion requirements, imaging findings, type of interventions, length of hospital stay, complications and outcomes on follow up. Results: Review of our institutional database identified 10 children with grade IV renal injury. Mean age was 11.7 ± 3.6 years (range, 6–18) and majority (6/10) were male. Motor vehicle collision and fall from heights were the commonest mechanisms of injury. While one patient responded to non-operative management, one girl needed emergency renal exploration and later nephrectomy. Eight needed minimally invasive interventions following initial non-operative management. One patient needed nephrectomy due to delayed hemorrhage while three patients needed delayed open reconstruction. The salvage rate in the group which needed interventions was 87.5% (7 of 8) however, the functional outcome was good only in 50% (4 of 8) of patients. The outcomes were better in those who were managed with MII earlier (3/4) compared to those who underwent delayed intervention (1/4). The median hospital stay was 11.5 days (range 7–34 days). Conclusion: Pediatric patients with non-exsanguinating grade IV renal injuries due to blunt trauma who fail non-operative management and need minimal invasive interventions have good renal salvage rates however, the functional outcomes are poorer. Judicious and early use of these minimally invasive interventions, instead of persisting with non-operative management can possibly improve these functional outcomes. Summary figure Summary figure